2015
DOI: 10.1186/s12958-015-0087-z
|View full text |Cite
|
Sign up to set email alerts
|

The HDL receptor SR-BI is associated with human prostate cancer progression and plays a possible role in establishing androgen independence

Abstract: BackgroundHuman prostate cancer represents one of the most frequently diagnosed cancers in men worldwide. Currently, diagnostic methods are insufficient to identify patients at risk for aggressive prostate cancer, which is essential for early treatment. Recent data indicate that elevated cholesterol levels in the plasma are a prerequisite for the progression of prostate cancer. Here, we analyzed clinical prostate cancer samples for the expression of receptors involved in cellular cholesterol uptake.MethodsWe s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 39 publications
10
65
0
Order By: Relevance
“…High SR-B1 expression has been demonstrated in diverse cancer cell lines and patient tumor samples [79][80][81] and correlates with worse patient survival [82]. SR-B1 can promote tumor progression through three different mechanisms.…”
Section: Sr-b1 Promotes Cancer Progression: Sr-b1 Antagonist As Anti-mentioning
confidence: 99%
“…High SR-B1 expression has been demonstrated in diverse cancer cell lines and patient tumor samples [79][80][81] and correlates with worse patient survival [82]. SR-B1 can promote tumor progression through three different mechanisms.…”
Section: Sr-b1 Promotes Cancer Progression: Sr-b1 Antagonist As Anti-mentioning
confidence: 99%
“…Twiddy et al (36) found that SR-BI downregulation caused a significant reduction in prostate-specific antigen production and decreased the viability of prostate cancer cell lines in vitro. Previous studies revealed that SR-BI was associated with more aggressive cancer phenotypes and could serve a tumor-promoting function in breast and prostate cancer (35,37). However, in gastric adenocarcinoma, the role of SR-BI appeared to be different.…”
Section: Sr-bi Expression % (N) -----------------------------------mentioning
confidence: 96%
“…The results of a previous study revealed that high SR-BI expression was an independent factor predictive of poor prognosis for patients with breast cancer (35). Schörghofer et al (37) reported that high SR-BI expression was associated with shorter disease-free survival times in prostate cancer. On the contrary, in gastric adenocarcinoma, patients with low SR-BI expression had significantly poorer prognosis than patients with high SR-BI expression, indicating that different mechanisms were involved.…”
Section: Sr-bi Expression % (N) -----------------------------------mentioning
confidence: 98%
“…It is well-known that SR-B1 is of vital importance in high-density lipoprotein (HDL)-cholesterol metabolism 6 and hepatitis C virus entry. [7][8][9] It has been reported that SR-B1 also plays a critical role in cancers including breast cancer, [10][11][12] prostate cancer, 13,14 and nasopharyngeal cancer. 15 The results showed that the expression of SR-B1 was highly up-regulated and SR-B1 functioned as an oncogene, promoting progression in these cancers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, high SR-B1 expression was significantly associated with poor clinical outcome in breast cancer 12 and prostate cancer. 14 However, expression and clinical value of SR-B1 in ccRCC has not been well addressed so far.…”
Section: Introductionmentioning
confidence: 99%